HADIST PENCIPTAAN PEREMPUAN DARI TULANG RUSUK (Analisis-Kritis Terhadap Pandangan Feminis) - Agusman, Ryandi (Jurnal Ushuluddin, 2019)
AbstracThis paper will further reveal the hadith about the creation of women from ribs by displaying various related hadith texts, capturing their sanad, analyzing their death through the comments of authoritative scholars. This study is a response to the feminist assumption that the hadith is gender biased or "mysoginist". From this it was found that sanad the hadith was authentic, because all the blessings were thsiqat. Although the hadith contains Israiliyat, it does not reduce its validity because it does not conflict with Aqeedah and Islamic teachings. This hadith is not in conflict with Qs. an-Nisa, verse: 1, is actually used as an explanation as contained in at-Tabari, Ibn Kathir, ar-Razi, and Thantawi. There are two views in interpreting the hadith, namely textual and metaphorical. The difference in how to interpret it is not tadhadd (contradictory) but only tanawwu '(diverse). In addition, the meaning does not necessarily make women inferior to men, because in the Islamic perspective, glory is not measured by the origin of creation. Therefore, the rejection and accusation of Muslim feminists related to the hadith is wrong.